Reproduction, growth and milk yield of Blended goats in Tanzania - Das, S.M. (1992)
Blended goats are a 3-way cross of meat goats, between Boer x Kamorai x Small East African goats; they constitute less than 5% or the 6 million goat population in Tanzania. Goats in the project were raised mainly on pastures with similar supplementation or concentrates at Kongwa and Malya stations. For 359 kids born between 1988 and 1990, mean weight at birth, weaning and 72 weeks of age averaged 2.7±0.02, 12.2±0.14 and 32.8±0.26 kg respectively. Birth type sex, season, location and age of dam significantly influenced birth and weaning weights but only birth type and location influenced live weight at 72 weeks of age. For 309 does that kidded between 1988 and 1990, mean age at first kidding was 26.6±0.27 months. Lactation milk yield, lactation length and butterfat averaged 148.3±2.17 kg, 186.3±3.25 days and 3.04% respectively. Season of kidding, age of doe, and location (Kongwa and Malya) influenced lactation milk yield and lactation length. The apparent fertility rate, fecundity rate and prolificacy rates were 64.3, 74.8 and 116.5%, respectively.